Saúde e qualidade de vida: um estudo comparativo em duas comunidades rurais no Estado do Paraná - Yamada, Roberto Shigueyasu (2012)
Any study on the tobacco production chain acknowledges that the weakest link in the process is the tobacco grower. In this case study, this complex topic was approached in an interdisciplinary perspective. It began with the contextualization of the tobacco growing farms as a specialized family-based agriculture, then an analogy of the tobacco leaf as two sides of a sustainable development: the good side related to the economic aspect, and the side of evil as the consequences on public health. And finally, the risks and the quality of life in the cultivation of tobacco. A semi-structured survey based on Surveillance of Risk and Protective Factors for Chronic Diseases by Telephone Inquiry (Vigitel) under the responsibility of the Secretariat of Health Surveillance, Ministry of Health was used to capture some information about the health of communities. The generic and self-perceptive instrument, Medical Outcomes Study 36 – short form health survey (SF-36), translated and validated into Portuguese, was used to verify whether there would be a difference in the quality of life in the health of two communities with different tobacco production systems: Itaiba with Burley type tobacco in the city of Marmeleiro – Pr, and Volta Grande with Virginea type tobacco in the city of Irati - Pr, and proved suitable in this survey. The reliability of the domains was assessed by using the Cronbach Alpha Coefficient, with results of 0.841 for Itaiba and 0.722 for Volta Grande. The validity of the domains was assessed through the Spearman Correlation, of which results were positive and statistically significant in most of the correlations in the two communities. There was no significant difference in Student’s t test when the variables location and agricultural activity were evaluated with individuals from the two communities, excluding retirees. A difference was observed when using pathologies such as Hypertension (HA), Diabetes (Db), cholesterol and osteoporosis as variables, compared to the dimensions that assessed the physical aspect. The individuals of the two communities are aware of the importance of the use of Personal Protective Equipment (PPE), but use it in a precarious way. The understanding of the risk involved in the work of tobacco growing is impaired when referring to oneself, as in other agricultural activities, the risks seem to only affect other individuals. With the monthly presence of the Community Health Agent (ACS), noticed by the monitoring of individuals with hypertension and diabetes in the Primary Care Information System (SIAB) of the Ministry of Health, as well as lower comsumption of self-medication, there is a better monitoring of the community population of Itaiba, city of Marmeleiro, in relation to the community of Volta Grande, city of Irati. The comparison of quality of life in health, with the same instrument in agricultural activity, may be performed in future developments of similar work.